BOSIVA AS AN ANDROID E-BOOK IN DISCUSSION OF ADAPTATION OF LIVING CREATURES FOR FIFTH GRADE OF ELEMENTARY SCHOOL - Pradana, Riki; Sofiyana, Marinda Sari; Putriani, Ida (JARES (Journal of Academic Research and Sciences), 2024)
Science subject in elementary school is a subject that invites students to reason about the surrounding natural conditions. The findings of the researchers indicate that there is a shortage of science learning facilities at several elementary schools in Blitar. As much as 84% of students in the observation stated that science lessons were difficult to understand. In addition, teachers and students who were interviewed stated that e-book teaching materials were interesting as science teaching materials, especially in materials on adaptation of living things to grade V SD. Therefore, researchers proposed Bosiva as a solution for developing new teaching materials in natural science material for adaptation of living things in digital form. This research is based on modified R&D which includes potential and problem formulation, data collection, product design, design validation, design revision, product testing, and product revision. Researchers developed Bosiva to find results for material expert validation of 86%, language validation of 93%, and media validation of 95% which all stated very feasible. In addition, the results of the teacher's readability test were 95% and the student's readability test was 97% which were also classified as very feasible. So, it can be concluded that Bosiva is a breakthrough in the development of android-based teaching materials to support learning adaptation of living things.